2022
DOI: 10.21511/im.18(2).2022.17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrinsic and extrinsic motivations on cyber-market mavenism: Their role in information-sharing behavior

Abstract: This paper aims to investigate the association between variables of intrinsic and extrinsic motivations, cyber-market mavenism, and information sharing behavior, particularly among social network sites (SNS) users in Iraq.This study depends on a quantitative method to test the variables. The sample contains 388 Iraqi customers or users using social network sites to share information about different products and services. The study conducts a purposive sample to determine the characteristics of users who have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…A market maven is an individual who possesses extensive knowledge about various products, purchasing options and market trends. They actively engage in conversations with customers, providing valuable market information and responding to customer inquiries (Abbas et al , 2022b; Feick and Price, 1987). Market mavens exhibit characteristics such as innovation, self-assurance, a continuous quest for consumer-oriented knowledge and a willingness to share information (Abbas et al , 2022a).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…A market maven is an individual who possesses extensive knowledge about various products, purchasing options and market trends. They actively engage in conversations with customers, providing valuable market information and responding to customer inquiries (Abbas et al , 2022b; Feick and Price, 1987). Market mavens exhibit characteristics such as innovation, self-assurance, a continuous quest for consumer-oriented knowledge and a willingness to share information (Abbas et al , 2022a).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…All of these studies show that the cultural aspect is an important factor in the market maven literature that needs to be further explored, especially in the social media domain. Researchers [3] also suggested to assess intrinsic and extrinsic motivations, as well as psychological aspects, as antecedents for market mavens sharing information, especially on social media (Figure 5).…”
Section: -3-thematical Analysismentioning
confidence: 99%
“…Researchers are in the process of constructing a recursive nomological network to thoroughly describe the causes and effects of mavenism. However, there is not much literature on mavenism in the cybermarket [3,4], and the body of literature remains open to further research. For instance, there is a growing body of literature on market mavens [4][5][6][7][8][9], while the majority of researchers have analyzed market mavens' search behavior without taking cross-store search behavior into account and thus underestimated responses to price promotions [10].…”
Section: -Introductionmentioning
confidence: 99%
“…Studies have supported their interest in technology; market mavens have a propensity to become e-mavens, also called online mavens, internet mavens and cyber mavens (e.g. Abbas et al , 2022; Barnes and Pressey, 2012; Farzin et al , 2020; Kiani and Laroche, 2019; Laughlin and MacDonald, 2010). However, understanding what exactly drives market mavens to use social media to share information is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Harrigan et al (2021), who identified market mavens' characteristics on social media, such as their number of followers and communication styles, suggested that future research should investigate market mavens' motivations for using social media for information provision. Motivations for sharing information are crucial factors in understanding market mavens' behavior (Abbas et al , 2022; Walsh et al , 2004). Thus, the present study investigated the underlying motivations for sharing fashion-related information.…”
Section: Introductionmentioning
confidence: 99%